Lockdown due to COVID-19 in Spanish Children Up to 6 Years: Consequences on Diet, Lifestyle, Screen Viewing, and Sleep - Mercedes Díaz-Rodríguez; Jesús Carretero-Bravo; Celia Pérez-Muñoz; Mercedes Deudero-Sánchez (Frontiers Media S.A., 2022)
Objectives: To record how the habits of children under 6 years of age in Cadiz have changed during lockdown, in order to identify those that could be a handicap for the problem of overweight and obesity.Methods: We developed a new questionnaire to analyse family living habits. The questionnaire was administered online to parents of children aged zero-six years. Eating habits, sedentary lifestyles, screen viewing, and sleep changes were evaluated.Results: Changes were found in family living habits, as shown by the results of McNemar's tests (p-value < 0.01 in all pairs except one, p-value = 0.097). A worsening of habits was also found to be more accentuated in families with low income, low educational level or small size of home. Some positive aspects associated with family meals and parental involvement were found.Conclusions: The lockdown has showed a significant break in the main routines of the children that could affect their health and may add to the worsening of the already poor childhood obesity situation. The positive aspects found can be instrumental in improving the situation in future similar situations.